Flow cytometric chromosome sorting in plants: the next generation - Vrána, Jan; Simková, Hana; Kubaláková, Marie; Cíhalíková, Jarmila; Doležel, Jaroslav (Methods (San Diego, Calif.), 2012)
Genome analysis in many plant species is hampered by large genome size and by sequence redundancy due to the presence of repetitive DNA and polyploidy. One solution is to reduce the sample complexity by dissecting the genomes to single chromosomes. This can be realized by flow cytometric sorting, which enables purification of chromosomes in large numbers. Coupling the chromosome sorting technology with next generation sequencing provides a targeted and cost effective way to tackle complex genomes. The methods outlined in this article describe a procedure for preparation of chromosomal DNA suitable for next-generation sequencing.
Keywords: Secale; polyploidie; Genome Size; Chromosomes, Plant; žito; průtoková cytometrie; genom rostlinný; hybridizace in situ fluorescenční; délka genomu; Germination; Seeds; Genome, Plant; ječmen (rod); fluorescenční mikroskopie; In Situ Hybridization, Fluorescence; vysoce účinné nukleotidové sekvenování; Metaphase; sekvenční analýza DNA; Microscopy, Fluorescence; Flow Cytometry; Sequence Analysis, DNA; umělé bakteriální chromozomy; semena rostlinná; Hordeum; Polyploidy; Triticum; High-Throughput Nucleotide Sequencing; pšenice; metafáze; klíčení; Chromosomes, Artificial, Bacterial; chromozomy rostlin